2005
DOI: 10.1126/science.1105978
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Saturn's Magnetosphere from MIMI During Cassini's Orbital Insertion

Abstract: The Magnetospheric Imaging Instrument (MIMI) onboard the Cassini spacecraft observed the saturnian magnetosphere from January 2004 until Saturn orbit insertion (SOI) on 1 July 2004. The MIMI sensors observed frequent energetic particle activity in interplanetary space for several months before SOI. When the imaging sensor was switched to its energetic neutral atom (ENA) operating mode on 20 February 2004, at approximately 10(3) times Saturn's radius RS (0.43 astronomical units), a weak but persistent signal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 164 publications
(146 citation statements)
references
References 15 publications
5
141
0
Order By: Relevance
“…Substantial electron fluxes in the 100 eV -2 keV energy range are present with measurable fluxes persisting up to energies of several keV. The Cassini MIMI instrument observed electrons with energies of many tens of keV near T5 (Krimigis et al 2005). When the spacecraft is sunlit the CAPS ELS observes spacecraft photoelectrons with energies less than about 5 eV, but for T5 this population disappeared when Cassini went through Titan's shadow in the time period near CA.…”
Section: Magnetospheric Electrons As a Source Of Titan's Ionospherementioning
confidence: 99%
See 1 more Smart Citation
“…Substantial electron fluxes in the 100 eV -2 keV energy range are present with measurable fluxes persisting up to energies of several keV. The Cassini MIMI instrument observed electrons with energies of many tens of keV near T5 (Krimigis et al 2005). When the spacecraft is sunlit the CAPS ELS observes spacecraft photoelectrons with energies less than about 5 eV, but for T5 this population disappeared when Cassini went through Titan's shadow in the time period near CA.…”
Section: Magnetospheric Electrons As a Source Of Titan's Ionospherementioning
confidence: 99%
“…Energetic electrons were observed in Saturn's outer magnetosphere by Voyager (Schardt et al 1984) and by both the CAPS ELS (Coates et al 2007b) and MIMI (Krimigis et al 2005) instruments onboard Cassini. Cravens et al (2006) suggested that incident electrons with a broad range of energies (25 eV -2000 keV) were needed to explain the ionospheric densities measured by the RPWS/LP and INMS during T5, and this has been confirmed by detailed calculations by Agren et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bunce et al, 2005;Dougherty et al, 2005;Gurnett et al, 2005;Young et al, 2005), now also including energetic neutral atom imaging of magnetospheric dynamics (e.g. Krimigis et al, 2005;Paranicas et al, 2005). Information on global dynamics can also be obtained from studies of polar UV auroras observed by the Hubble Space Telescope (HST), at both Jupiter (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Dougherty et al, 2005;Krimigis et al, 2005;Young et al, 2005), by ground-based IR Doppler measurements of ionospheric flows (Stallard et al, 2004), and by studies of the planet's aurorae using the Hubble Space Telescope (HST) (e.g. Gérard et al, 1995Gérard et al, , 2004Cowley et al, 2004a;Prangé et al, 2004).…”
Section: Introductionmentioning
confidence: 99%